Antioxidant, Cytotoxic, and Antimicrobial Potential of Silver Nanoparticles Synthesized using Tradescantia pallida Extract - Shahzadi, Irum; Aziz Shah, Syed Munawar; Shah, Mohammad Maroof; Ismail, Tariq; Fatima, Nighat; Siddique, Maria; Waheed, Ummara; Baig, Ayesha; Ayaz, Aisha (Frontiers in Bioengineering and Biotechnology, 2022)
Silver nanoparticles have received much attention, due to their wide range of biological applications as an alternative therapy for disease conditions utilizing the nanobiotechnology domain for synthesis. The current study was performed to examine the antioxidant, anticancer, antibacterial, and antifungal potential of biosynthesized silver nanoparticles (TpAgNPs) using plant extract. The TpAgNPs were produced by reacting the Tradescantia pallida extract and AgNO3 solution in nine various concentration ratios subjected to bioactivities profiling. According to the current findings, plant extract comprising phenolics, flavonoids, and especially anthocyanins played a critical role in the production of TpAgNPs. UV–visible spectroscopy also validated the TpAgNP formation in the peak range of 401–441 nm. Further, the silver ion stabilization by phytochemicals, face-centered cubic structure, crystal size, and spherical morphology of TpAgNPs were analyzed by FTIR, XRD, and SEM. Among all TpAgNPs, the biosynthesized TpAgNP6 with a medium concentration ratio (5:10) and the plant extract had effective antioxidant potentials of 77.2 ± 1.0% and 45.1 ± 0.5% free radical scavenging activity, respectively. The cytotoxic activity of TpAgNP6 in comparison to plant extract for the rhabdomyosarcoma cell line was significantly the lowest with IC50 values of 81.5 ± 1.9 and 90.59 ± 1.6 μg/ml and cell viability % of 24.3 ± 1.62 and 27.4 ± 1.05, respectively. The antibacterial and antifungal results of TpAgNPs revealed significant improvement in comparison to plant extract, i.e., minimum inhibition concentration (MIC) 64 μg/ml against Gram-negative Pseudomonas aeruginosa while, in the case of antifungal assay, TpAgNP6 was active against Candida parapsilosis. These TpAgNPs play a crucial role in determining the therapeutic potential of T. pallida due to their biological efficacy.